Experiences, attitudes, and prospects of Malaysian Muslim and Christian students on dialogue / Simon Herrmann - Simon , Herrmann (2024)
What are prospects for Muslim-Christian dialogue among those who are likely to be in positions of influence in the future? This is the question behind the original research on which this dissertation is based. Postgraduate Muslim and Christian students of various universities and seminaries in Malaysia were interviewed about their experiences with people of the other faith, the benefits, need and difficulties in regard to dialogue and their personal interest in it. Analysis took place by basic statistical methods, content analysis and comparative analysis. Results show that there are obstacles that have a detrimental effect on dialogue. Among them are that students have limited contact with those of the other faith, Muslims do not want to be accused of taking steps towards compromising their faith and Christian students are concerned that their contact with Muslims could be interpreted in a way of propagating their faith to Muslims. Nevertheless, the students are not interested in living segregated lives. Openness on both sides for various modes of dialogue is high – higher than they would think it is. This dissertation concludes that the students find open doors for dialogue among those of the other faith and that they as prospective future leaders of their religious communities have many opportunities to move dialogue forward if they desire to do so. By laying open the attitudes, hopes, interests and concerns the findings of this study can be used to find ways how dialogue can be conducted successfully. In the Conclusion some steps toward implementation are suggested. The findings have significance for the students themselves, the religious communities they are part of and for all those who are interested in Muslim-Christian dialogue in Malaysia.